Enhancing drought resistance in Pinus tabuliformis seedlings through root symbiotic fungi inoculation - Xu, Lingjie; He, Jiadong; Meng, Yu; Zheng, Yanyan; Lu, Bin; Zhang, Jiawen; Zhou, Yong (Frontiers in Plant Science, 2024)
Background: Drought constitutes a major abiotic stress factor adversely affecting plant growth and productivity. Plant-microbe symbiotic associations have evolved regulatory mechanisms to adapt to environmental stress conditions. However, the interactive effects of different fungi on host growth and stress tolerance under drought conditions remain unclear.Objective: This study explored the effects of varying polyethylene glycol (PEG-6000) concentrations (0%, 15%, 25%, and 35%) on the growth and physiological responses of two ectomycorrhizal fungi (Suillus granulatus (Sg) and Pisolithus tinctorius (Pt)) and two dark septate endophytes (Pleotrichocladium opacum (Po) and Pseudopyrenochaeta sp. (Ps)) isolated from the root system of Pinus tabuliformis. Specifically, the study aimed to evaluate six inoculation treatments, including no inoculation (CK), single inoculations with Sg, Pt, Po, Ps, and a mixed inoculation (Sg:Pt:Po:Ps = 1:1:1:1), on the growth and physiological characteristics of P. tabuliformis seedlings under different water regimes: well-watered at 70% ± 5%, light drought at 50% ± 5%, and severe drought at 30% ± 5% of the maximum field water holding capacity.Results: All four fungi exhibited the capacity to cope with drought stress by enhancing antioxidant activities and regulating osmotic balance. Upon successful root colonization, they increased plant height, shoot biomass, root biomass, total biomass, and mycorrhizal growth response in P. tabuliformis seedlings. Under drought stress conditions, fungal inoculation improved seedling drought resistance by increasing superoxide dismutase and catalase activities, free proline and soluble protein contents, and promoting nitrogen and phosphorus uptake. Notably, mixed inoculation treatments significantly enhanced antioxidant capacity, osmotic adjustment, and nutrient acquisition abilities, leading to superior growth promotion effects under drought stress compared to single inoculation treatments.All four fungi tolerated PEG-induced drought stress, with increased antioxidant enzyme activities and osmotic adjustment substances and they promoted the growth and enhanced drought resistance of P. tabuliformis seedlings.